2018
DOI: 10.1017/s2040174418000648
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of adverse childhood experiences via maternal depression and anxiety and moderation by child sex

Abstract: Adverse childhood experiences (ACEs) of parents are associated with a variety of negative health outcomes in offspring. Little is known about the mechanisms by which ACEs are transmitted to the next generation. Given that maternal depression and anxiety are related to ACEs and negatively affect children's behaviour, these exposures may be pathways between maternal ACEs and child psychopathology. Child sex may modify these associations. Our objectives were to determine: (1) the association between ACEs and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 85 publications
7
118
3
Order By: Relevance
“…Letourneau et al 19 tested the theory of intergenerational transmission of stress and found maternal adverse childhood experiences were predictive of mood and anxiety during pregnancy and postpartum, and externalising problems in the children, especially boys. Aylott et al 20 further confirmed this opposite-sex-specific parent-of-origin effect in the etiology of psychotic symptoms.…”
Section: Early Adversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Letourneau et al 19 tested the theory of intergenerational transmission of stress and found maternal adverse childhood experiences were predictive of mood and anxiety during pregnancy and postpartum, and externalising problems in the children, especially boys. Aylott et al 20 further confirmed this opposite-sex-specific parent-of-origin effect in the etiology of psychotic symptoms.…”
Section: Early Adversitymentioning
confidence: 99%
“…Given that maternal anxiety and depression are related to adverse childhood experiences and negatively affect children’s behaviour, 16 18 these exposures provide potential pathways between maternal adverse childhood experiences and child psychopathology. Letourneau et al 19 tested the theory of intergenerational transmission of stress and found maternal adverse childhood experiences were predictive of mood and anxiety during pregnancy and postpartum, and externalising problems in the children, especially boys. Aylott et al 20 .…”
Section: Themed Issue: Spotlight On Dohad Research In Canadamentioning
confidence: 99%
“…Early experiences in childhood impact how adults later parent their own children (Letourneau et al, 2019). Some adults may have experienced adverse childhood experiences (ACEs), events that occur in a child's life before the age of 18 and include trauma related to household dysfunction, neglect, or abuse (Felitti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Some adults may have experienced adverse childhood experiences (ACEs), events that occur in a child's life before the age of 18 and include trauma related to household dysfunction, neglect, or abuse (Felitti et al, 1998). Parents who have been exposed to ACEs are more likely to expose their own children to ACEs (Felitti et al, 1998;Larkin, Shields, & Anda, 2012;Letourneau et al, 2019). The effects of ACEs may be longterm, with poorer mental, physical, and behavioral outcomes in adulthood (Anda et al, 2006;Crouch, Strompolis, Bennett, Morse, & Radcliff, 2017;Felitti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, a growing body of social psychological research has established that distressing parental emotions—primarily depression, anxiety, or combined measures of anger and aggression—negatively impact children’s emotional and behavioral development (Cohen, ; Galambos et al, ; Letourneau et al, ; Mirowsky & Ross, ; Moretti et al, ).…”
Section: Introductionmentioning
confidence: 99%